Interlanguage Errors In Writing Descriptive Text Made By 10th Grade Students Of SMA Negeri 1 Wuryantoro In 2014/2015 Academic Year - Widyantoro, Widyantoro, Prof. Dr. Endang Fauziati, M. Hum, Nur Hidayat, M. Pd (2015)
This study aims to describe the types of lexical errors, syntactical errors and discourse errors made by 10th grade students of SMA Negeri 1 Wuryantoro; explain the frequency of each types of errors and describe the dominant type of errors; and identify the sources of error. The type of this research is descriptive qualitative research. In collecting data the researcher used elicitation technique. The steps that the researcher used in collecting the data are; the researcher asked the students to make a descriptive text, the researcher collected the data and marked the errors that occurred in students' writing and documented the erroneous and classified the errors based on the theory of linguistic category and surface strategy taxonomy to classify the errors. The result of this research are lexical errors (86 errors or 24, 85%). The errors are classified into wrong spelling (60 errors or 17, 34%), use Indonesian word/code switching (11 errors or 3, 17%) and false friend (15 errors or 4, 33%). The second is syntactical errors (238 errors or 68, 78%). The errors classified into twenty one errors namely: redundancy of phrase (7 errors or 2, 02%), misordering of phrase (31 errors or 8, 95%), omission of {-s} as plural marker (10 errors or 2, 89%), the use of verb tense from omission of {-s} in present singular form (16 errors or 4, 62%), the use of verb tense from omission of {-'s} in possessive form (5 errors 1, 44%), the use of verbing in present form (6 errors 1, 73%), misuse of have/has (18 errors or 5, 20%), omission of BE as full verb (47 errors or 13, 58%), addition of BE as full verb (4 errors or 1, 15%), misuse of BE (17 errors or 4, 91%), addition of article (17 errors or 4, 91%), omission of article (5 errors or 1, 44%), misuse of article (4 errors or 1, 15%), the use of pronoun from objective for subjective (3 errors or 0, 86%), the use of pronoun from subjective for possessive adjective (12 errors or 3, 46%), the use of pronoun from subjective for objective (7 errors or 2, 02%), the use of pronoun from possessive adjective for subjective (3 errors or 0, 86%), the use of pronoun from objective for possessive adjective (5 errors or 1, 44%), the use of pronoun from possessive adjective to objective (2 errors or 0, 57%), omission of preposition (13 errors or 3, 75%) and misuse of preposition (5 errors or 1, 44%). The third is discourse errors (22 errors or 6, 35%). Those errors classified into: generic structure (3 errors 0, 86%), references (15 errors or 4, 33%) and addition of conjunction (4 errors or 1, 15%). The researcher also found two sources of error in this research namely, interlingual errors and intralingual errors.